2019
DOI: 10.1155/2019/8659302
|View full text |Cite
|
Sign up to set email alerts
|

Implication of IL-17 in Bone Loss and Structural Damage in Inflammatory Rheumatic Diseases

Abstract: Proinflammatory cytokines play an important role in the systemic and focal bone loss associated with chronic inflammatory diseases. Targeting these cytokines with biologics and small molecules has led to a major improvement of the bone health of patients with inflammatory arthritis. Cytokines from the IL-17 family have been shown to be involved in the pathogenesis of several diseases such as spondyloarthritis, psoriatic arthritis, or psoriasis. IL-17A has been the first described and the most studied. The rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 60 publications
0
25
1
Order By: Relevance
“…This nding is partly consistent with a study by Li et al [27] who found a direct relationship between IL-17A and DAS28 scores in rheumatoid arthritis patients. Indeed, high IL-6 and IL-17 has been implicated in higher DAS28 scores, which together correlate with radiographical progression of RA patients [28][29][30][31]. Nonetheless, contrary to our study, Chung et al [32], using enzyme-linked immunosorbent assay, reported no signi cant correlation between IL-6 and DAS28 scores.…”
Section: Discussioncontrasting
confidence: 88%
“…This nding is partly consistent with a study by Li et al [27] who found a direct relationship between IL-17A and DAS28 scores in rheumatoid arthritis patients. Indeed, high IL-6 and IL-17 has been implicated in higher DAS28 scores, which together correlate with radiographical progression of RA patients [28][29][30][31]. Nonetheless, contrary to our study, Chung et al [32], using enzyme-linked immunosorbent assay, reported no signi cant correlation between IL-6 and DAS28 scores.…”
Section: Discussioncontrasting
confidence: 88%
“…This finding is partly consistent with a study by Li et al [ 32 ] who found a direct relationship between IL-17A and DAS28 scores in rheumatoid arthritis patients. Indeed, high IL-6 and IL-17 have been implicated in higher DAS28 scores, which together correlate with radiographical progression of RA patients [ 33 36 ]. Nonetheless, contrary to our study, Chung et al [ 37 ], using enzyme-linked immunosorbent assay, reported no significant correlation between IL-6 and DAS28 scores.…”
Section: Discussionmentioning
confidence: 99%
“…In postmenopausal osteoporosis patients, serum IL-17A is significantly higher, while the IFN-γ and IL-4 are significantly lower, suggesting osteoporosis may be more associated with the Th17 cells rather than the Th1 or Th2 cells (Zhang et al, 2015 ). The further study demonstrates IL-17A is pro-osteoclastogenic at the cellular level (Le Goff et al, 2019 ). In vivo study shows that although IL-17A is not required for normal bone homeostasis, it plays a vital role in bone loss of ovariectomized osteoporosis mouse models.…”
Section: Bm-controlled Immune Systemmentioning
confidence: 96%
“…In vivo study shows that although IL-17A is not required for normal bone homeostasis, it plays a vital role in bone loss of ovariectomized osteoporosis mouse models. Furthermore, preliminary data from clinical trials show that anti-IL-17A antibodies stabilize bone density in inflammatory arthritis (Le Goff et al, 2019 ). These results suggest an inter-relationship between osteoporosis and neurodegenerative diseases.…”
Section: Bm-controlled Immune Systemmentioning
confidence: 99%